The role of temporal intervals on reinforcer accumulation. Issue 3 (25th October 2017) - French, Eric J.; Reilly, Mark P.
Abstract : Animals accumulate reinforcers when they forgo the opportunity to consume available food in favor of acquiring additional food for later consumption. Laboratory research has shown that reinforcer accumulation is facilitated when an interval (either spatial or temporal) separates earning from consuming reinforcers. However, there has been no systematic investigation on the interval separating consuming reinforcers from earning additional reinforcers. This oversight is problematic because this second interval is an integral part of much of the previous research on reinforcer accumulation. The purpose of the current study was to determine the independent contributions of these two temporal intervals on reinforcer accumulation in rats. Each left lever press earned a single food pellet; delivery of the accumulated pellet(s) occurred upon a right lever press. Conditions varied based on the presence of either an intertrial interval (ITI) that separated pellet delivery from the further opportunity to accumulate more pellets, or a delay‐to‐reinforcement that separated the right lever press from the delivery of the accumulated pellet(s). Delay and ITI values of 0, 5, 10 and 20 s were investigated. The delay‐to‐reinforcement conditions produced greater accumulation relative to the ITI conditions, despite accumulation increasing the density of reinforcement more substantially in the ITI conditions. This finding suggests that the temporal separation between reinforcer accumulation and subsequent delivery and consumption was a more critical variable in controlling reinforcer accumulation.